The awareness and understanding of waqf among UiTM Puncak Alam Students / Muhamad Hakimi Zulkifili - Zulkifili, Muhamad Hakimi (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This study aims to identify awareness and understanding among students in UiTM Puncak Alam regarding waqf . An understanding of the importance of waqf and how waqf work is important as students are the pillar supporting the charitable institutions In the future. In fact, the lack of student awareness will affect the development of waqf. The research conducted is in the form of field research implemented through survey among UiTM Puncak Alam from varies faculty. In addition, review of literature was performed as part of the study. The study focuses on the awareness and understanding of the students in UiTM Puncak Alam on waqf property. Overall, the Muslim community has awareness regarding the waqf propery, however, the understanding of the waqf property still needs to be improved. Efforts to increase awareness and understanding of the relevant endowment should be varied with an effective approach to optimized endowment role in community development, particularly in IPT.